Music Practices Across Borders : (E)Valuating Space, Diversity and Exchange - Hondros, Konstantin; Peres da Silva, Glaucia (Musik und Klangkultur, 2019)
Reconnecting migration studies and the theory of valuation, this collection offers an interdisciplinary approach to the study of transnational music practices. Music is here approached as a practice not confined by audibility - rather, it is "seen" when the YouTube video is clicked, "felt" when the subwoofer vibrates, and "smelled" when the festival crowd dances: practices make music emerge in concrete situations constituted by people, objects, techniques, meanings, and emotions. Through these practices, values are created and shared which connect a way of music-making with objects and places of experiencing music unconfined by borders of any kind.